The Role of Transformational Leadership and Psychological Capital Towards Knowledge Sharing in Cirebon City State High School Educational Institutions - Thoriq, Muhammad; Rahayuningsih, Amelia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study discusses the role of transformational leadership and psychological capital in knowledge sharing in educational institutions. This research focuses on leadership processes, especially in the education sector, and shows the influence of leadership and knowledge sharing in fostering innovative behavior. The research method involves quantitative analysis with a focus on high schools in Cirebon, Indonesia. Results show a strong correlation between transformational leadership, psychological capital, and knowledge sharing in stimulating innovative behavior.